1979
DOI: 10.1210/endo-105-4-911
|View full text |Cite
|
Sign up to set email alerts
|

Acute Self-Suppression of Corticosteroidogenesis in Isolated Adrenocortical Cells*

Abstract: The relation between steroidogenesis induced by ACTH and that induced by exogenous concentrations of glucocorticoids was studied in isolated adrenocortical cells. Exogenous corticosterone and cortisol, in concentrations within the production capacity of the adrenal gland, suppressed steroidogenesis induced by ACTH in rat and beef cells, respectively. The precursors pregnenolone and progesterone enhanced steroidogenesis in both rat and beef cells. Aldosterone in rat cells and 17 beta-estradiol in rat and beef c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 29 publications
2
19
0
1
Order By: Relevance
“…With respect to the effect of CORT on the adrenal steroidogenic activity, a number of in vitro and in vivo studies have shown a decrease in adrenal responsiveness following prior exposure to stressors or ACTH. For example, experiments in cultured adrenal cells have shown that ACTH-induced CORT synthesis is rapidly inhibited (within 1-2 h) when CORT is added to the medium at high concentration (Peron et al 1960, Carsia & Malamed 1979. This is in accordance with studies in vivo in the rat showing that previous exposure to a stressor, or to a high concentration of ACTH, inhibits CORT synthesis in response to further stimuli (Langecker & Lurie 1957, Jones & Stockham 1966, suggesting that CORT synthesis is dependent on the prior state of adrenal activity.…”
Section: Intra-adrenal Glucocorticoid-mediated Negative Feedbacksupporting
confidence: 73%
“…With respect to the effect of CORT on the adrenal steroidogenic activity, a number of in vitro and in vivo studies have shown a decrease in adrenal responsiveness following prior exposure to stressors or ACTH. For example, experiments in cultured adrenal cells have shown that ACTH-induced CORT synthesis is rapidly inhibited (within 1-2 h) when CORT is added to the medium at high concentration (Peron et al 1960, Carsia & Malamed 1979. This is in accordance with studies in vivo in the rat showing that previous exposure to a stressor, or to a high concentration of ACTH, inhibits CORT synthesis in response to further stimuli (Langecker & Lurie 1957, Jones & Stockham 1966, suggesting that CORT synthesis is dependent on the prior state of adrenal activity.…”
Section: Intra-adrenal Glucocorticoid-mediated Negative Feedbacksupporting
confidence: 73%
“…The time of onset for this effect was reported to be 30-40 minutes, significantly longer than the time required for catecholaminergic substances to exert a vasodilatory effect (Harrison and Hoey, 1960). The association between the corticosteroidogenic effect of ACTH and an increase in adrenal blood flow has subsequently been noted by several authors (Carsia and Malamed, 1979;Maier and Staehelin, 1968;Sibley et al, 1981;Vinson et al, 1985a). The short-term effects of ACTH, which involve an immediate increase in corticosterone secretion, are reported to start within 10 minutes of administration, with the peak effect evident within 15-30 minutes of administration (Bassett and Pollard, 1980;Nussdorfer et al, 1984).…”
Section: Regulation Of Arterial Blood Flowmentioning
confidence: 94%
“…These interacting cascades of genomic and nongenomic events work in combination to activate and maintain optimal levels of steroidogenic proteins, ultimately leading to mitochondrial import of cholesterol and CORT synthesis. In addition, our recent mathematical modeling of the CORT response to ACTH suggests that a rapid, intra-adrenal CORT negative feedback loop constitutes an additional control mechanism of steroidogenesis (14)(15)(16)(17). The biological processes underlying this self-inhibition are not known, but the glucocorticoid receptor (GR) is expressed in the adrenal cortex (15,18).…”
mentioning
confidence: 99%